ANALISIS POTENSI DAN STRATEGI PENGEMBANGAN OBJEK WISATA AIR PANAS GAMPONG TERUJAK KECAMATAN SERBAJADI KABUPATEN ACEH TIMUR - Erwin Syahputra; Cut Maila Hanum; Kurniawati (LPPM STIK Pante Kulu, 2022)
This research aims to obtain data regarding supporting factors as well as obstacles in thedevelopment of tourism object of Terujak Village Hot Spring, and to analyse possiblestrategies that can be implemented by the local community in developing the tourism objectof Terujak Village Hot Spring, and to increase tourists visits. The research was located attourism object of Terujak Village Hot Spring, Serbajadi Sub-District of Aceh TimurRegency. The research was conducted for two months from January until February of 2019.Method used for the data analysis is descriptive with qualitative approach, and SWOTanalysis is used to obtain development strategy. The results of the analysis using matrixIFAS-EFAS demonstrates that the number of strengths and threats achieved the smallestnumber (-0,82) resulting in ST as the selected strategy. Based on SWOT diagram, strategyin quadran II which is ST strategy is a strategy that utilize strength factor to overcomethread factor.